Physical Aging of an Epoxy Resin for Civil Engineering Applications from Fast Scanning Calorimetry Investigations. Issue 1 (21st October 2022) - Quelennec, Blandine; Delpouve, Nicolas; Delbreilh, Laurent; Delannoy, Romain; Richaud, Emmanuel
Abstract: This works deals with the structural relaxation of an epoxy resin based on bisphenol A diglycidyl ether polymer (DGEBA) and 4, 7, 10‐Trioxa‐1, 13‐tridecanediamine (TTDA) hardener. The physical aging experiments are performed in situ using fast scanning calorimetry (FSC). The profile of the relaxation enthalpy with temperature is obtained close to the glass transition by annealing the resin during 10 min at various aging temperatures. From this profile, the structural relaxation is probed at various distances from the glass transition temperature, with aging times ranging from 0 to 1000 min. The Tool–Narayanaswamy–Moynihan (TNM) model is employed to analyze the relaxation data.